Evidence and certainty in Lisu - Bradley, David (2024)
This paper presents data on epistemic and evidential markers in three main varieties and several subvarieties of Lisu, a Tibeto-Burman language with over a million speakers in China, Burma, Thailand and India. It is shown that the original system had a number of epistemic markers and a reported speech marker, along with various imperative and question markers, all in clause-final position. These markers have similar meanings in those varieties which have not undergone change. In some varieties and subvarieties, evidential systems have developed separately over the last couple of hundred years, grammaticalising some verbs and redeploying some epistemics into evidentials. The corresponding systems in the most closely-related languages show cognates for the reported speech marker, some epistemic markers and some other final markers for imperatives and questions, and for the verbs which grammaticalise into evidentials in Lisu. It is clear that the direction of change in Lisu is from epistemic to evidential, and that these developments are relatively recent and separate, for example from the development of the evidential system of Akh